Clopidogrel Versus Ticagrelor or Prasugrel After Primary Percutaneous Coronary Intervention According to CYP2C19 Genotype: A POPular Genetics Subanalysis. (April 2021) - Claassens, Daniel M.F.; Bergmeijer, Thomas O.; Vos, Gerrit J.A.; Hermanides, Renicus S.; van 't Hof, Arnoud W.J.; van der Harst, Pim; Barbato, Emanuele; Morisco, Carmine; Tjon Joe Gin, Richard M.; Asselbergs, Folkert W.; Mosterd, Arend; Herrman, Jean-Paul R.; et al.
Abstract : Background: Guidelines favor ticagrelor or prasugrel over clopidogrel in patients with myocardial infarction. However, the POPular Genetics trial (Patient Outcome After Primary Percutaneous Coronary Intervention [PCI]) showed that in patients with primary PCI, a CYP2C19 genotype–guided strategy was associated with a lower bleeding risk without increasing thrombotic risk, compared with routine ticagrelor/prasugrel treatment. Nevertheless, optimal P2Y12 inhibitor treatment in specific CYP2C19 genetic subgroups is still a subject of debate. Methods: A prespecified subanalysis of the POPular Genetics trial was performed, using patients in whom CYP2C19 *2, *3, and *17 genotypes was determined. Two different analyses were planned. The first assessed the effect of the CYP2C19 *17 allele in clopidogrel-treated patients. The second compared the effect of clopidogrel in noncarriers of a loss-of-function allele with ticagrelor/prasugrel–treated patients, irrespective of CYP2C19 genotype. Main outcomes were a thrombotic outcome (cardiovascular death, myocardial infarction, stent thrombosis, and stroke) and a bleeding outcome (PLATO [Platelet Inhibition and Patient Outcomes] major and minor bleeding) after 12 months. Results: A total of 2429 patients were used for analyses. In the first analysis, the CYP2C19 *17 polymorphism was not found to have a significant influence on thrombotic (adjusted hazard ratio, 0.95 [95% CI, 0.45–2.02]) or bleeding outcomes (adjusted hazard ratio, 0.74 [95% CI, 0.48–1.18]). In the second analysis, clopidogrel was associated with a lower number of bleeding events compared with ticagrelor/prasugrel (9.9% versus 11.7%, adjusted hazard ratio, 0.74 [95% CI, 0.56–0.96]), without a significant increase in thrombotic events (3.4% versus 2.5%, adjusted hazard ratio, 1.14 [95% CI, 0.68–1.90]). Conclusions: In patients with primary PCI not carrying a CYP2C19 loss-of-function allele, the use of clopidogrel compared with ticagrelor or prasugrel was associated with lower bleeding rates, without an increase in thrombotic events. No effect on clinical outcomes was found for the CYP2C19 *17 polymorphism. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01761786. URL: https://www.trialregister.nl/ ; Unique identifier: NL2872. Abstract : Supplemental Digital Content is available in the text.